Addakhiil Bahasa Arab yang Berasal dari Bahasa Indonesia dalam Kitab Mu’jam Ad-Dakhiil Fii Al-Lughah Al-Arabiyyah Al-Hadiitsah wa Lahjaatihaa - Muhamad Izzul Fiqih; Tuti Hardianti Hasibuan; Neldi Harianto; Eva Iryani; Sahrizal Vahlepi (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
This study aims to determine whether or not Indonesian vocabulary has been absorbed into Arabic The researchmethodology used in this research is descriptive qualitative. The data obtained in this study is data taken from a book entitled Ad-Dakhiil Fii Al-Lughah Al-Arabiyyah Al-Hadiitsah Wa Lahjaatihaa. The researcher took data with Indonesian criteria which were absorbed into Arabic in the book, entered it into the data record, then the researcher conducted a descriptive analysis of the data. Based on the data obtained and through a literature review of various relevant literature, as well as an analysis of matters relating to research problems, it was found that 11 Indonesian vocabularies were absorbed into Arabic in the book Mu'jam Ad-Dakhiil Fii AlLughah Al -Arabiyyah Al-Hadiitsah Wa Lahjaatihaa by Sheikh Vaniyambadi Abdur Rahim. The vocabulary includes gelatin, Indonesia, bamboo, exchange, kitchen, rupiah, Singapore, soy sauce, cassowary, fluent, mango. This shows that it is true that there is a synergistic relationship between Arabic and Indonesian.